Weed anatomy - Kraehmer, Hansjoerg; Baur, Peter, 1965-; Wiley eBooks (Chicester : Wiley, 2013)
Essential for all weed scientists, this book provides fully comprehensive coverage, including the world's fifty commercially most important species, with detailed, full color photographs throughout. Beginning with a general overview of weed anatomy, structured in a way similar to other classical plant anatomy textbooks, this book discusses monocots, dicots, brackens and horsetails with special reference to their anatomy. Plant scientists will appreciate the depth of detail found in this book.
Weed Anatomy Monograph 3: Amaranthus retroflexus L. and Amarantus palmeri S. Wats. Introduction; The shoot; The leaf; The root; Weed Anatomy Monograph 4: Ambrosia artemisiifolia L.; Introduction; The shoot; The root; The leaf; Weed Anatomy Monograph 5: Apera spica-venti (L.) P. Beauv.; Weed Anatomy Monograph 6: Avena fatua L. and Avena sterilis L.; Introduction; The shoot; The leaf; The root; Weed Anatomy Monograph 7: Bidens pilosa L. and Bidens tripartita L.; Introduction; The shoot; The root; Weed Anatomy Monograph 8: Bromus secalinus L., Bromus sterilis L. and Bromus tectorum L.
Introduction.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Weeds -- Anatomy; SCIENCE -- Life Sciences -- Biology -- General; TECHNOLOGY & ENGINEERING -- Agriculture -- General; Electronic books